Renewable Energies and Water Security:: Thermo Solar Energy as an Alternative for Seawater Desalination in North Africa and the Middle East - Souza, Luiz Enrique Vieira de; Ferreira, Leila da Costa (Sustainability in Debate, 2016)
Climate change-related events, added to estimations about economical and population growth ”“ tend to aggravate water scarcity, which is already affecting almost every country in the North of Africa and the Middle East. Based on a critical analysis of the “ACQUA-CSP” report, we discuss the initiatives devoted to the mitigation of water stress in these regions, with an emphasis on the seawater desalination processes. Since existing desalination plants are currently powered by fossil fuels, the use of thermo solar energy will be introduced as a sustainable strategy for the increase of water supply. We conclude that, in order to achieve the successful management of water resources, engineering and infrastructure solutions must be oriented by democratic institutions able to mediate conflicts over the allocation of water resources.